2022
DOI: 10.1128/spectrum.01899-22
|View full text |Cite
|
Sign up to set email alerts
|

Alterations in the Gut Microbiota and Metabolomics of Seafarers after a Six-Month Sea Voyage

Abstract: Maintaining the health of seafarers undertaking long-term voyages is a difficult task. Apart from the alterations in the gut microbiome and fecal metabolites after a long-term voyage, our study also revealed that 20 differential metabolites within six differentially enriched human metabolic pathways are worthy of attention.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 44 publications
0
2
0
Order By: Relevance
“…Previous research has also indicated an association between gut microbiota imbalance and certain mental disorders such as anxiety and depression. Jiang’s high-throughput sequencing analysis of 46 depressed patients and 30 healthy controls showed significantly higher abundance of Actinobacteria and Firmicutes in the healthy control group at the phylum level compared to the depressed patients ( 27 ). Moreover, previous MR studies have indicated a protective effect of Actinobacteria against major depressive disorder (MDD) incidence (OR 0.88, 95% CI 0.87-0.9) ( 28 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous research has also indicated an association between gut microbiota imbalance and certain mental disorders such as anxiety and depression. Jiang’s high-throughput sequencing analysis of 46 depressed patients and 30 healthy controls showed significantly higher abundance of Actinobacteria and Firmicutes in the healthy control group at the phylum level compared to the depressed patients ( 27 ). Moreover, previous MR studies have indicated a protective effect of Actinobacteria against major depressive disorder (MDD) incidence (OR 0.88, 95% CI 0.87-0.9) ( 28 ).…”
Section: Discussionmentioning
confidence: 99%
“…It is worth mentioning that depressed patients often have lower levels of omega-3 fatty acids ( 33 ). While there is no consensus on whether supplementing omega-3 alone can effectively alleviate depression, it has been observed that consuming omega-3-rich fish may be associated with increased abundance of Holdemanella genus ( 27 ). Could increasing the abundance of Holdemanella genus and reducing the risk of postpartum depression be achieved through omega-3 supplementation?…”
Section: Discussionmentioning
confidence: 99%